2020
DOI: 10.1002/agj2.20319
|View full text |Cite
|
Sign up to set email alerts
|

Sand‐capping depth and subsoil influences on ‘Tifway’ bermudagrass response to irrigation frequency and drought

Abstract: Golf courses and sports fields with turfgrass surfaces have been moving toward sand-based root zone construction to enhance playability. Sand-capped systems are ideally suited for situations where poor water quality and/or clayey soils necessitate rapid drainage and the need to flush salts. This study evaluated sandcapping depth and subsoil texture on dynamics and availability of water as well as subsequent turf canopy and rooting characteristics. Objectives of this study were (a) to assess season-long turf pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…diminished conditions when grown on fine-textured native soil and irrigated with water high in sodium or salts (Dyer et al, 2020). Sand capping the existing native soil has become an increasingly used practice to deal with poor water quality or excessive rainfall, because it provides an improved, welldraining growing medium for turfgrass, leading to improved performance and playability (White, 2013;Whitlark & Isom, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…diminished conditions when grown on fine-textured native soil and irrigated with water high in sodium or salts (Dyer et al, 2020). Sand capping the existing native soil has become an increasingly used practice to deal with poor water quality or excessive rainfall, because it provides an improved, welldraining growing medium for turfgrass, leading to improved performance and playability (White, 2013;Whitlark & Isom, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Limited published data are available concerning irrigation of sand-capped systems. Dyer et al (2020) found no differences in percentage green cover between 1 vs. 2 d wk −1 irrigation frequency regimes supplying 60% of reference evapotranspiration (ET o ) on sand-capped 'Tifway' hybrid bermudagrass [Cynodon dactylon L. (Pers.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) and Dyer et al. (2020). We would like to thank Dr. John Stier, University of Tennessee, and Dr. Mike Richardson, University of Arkansas, who served as editors for this special issue.…”
mentioning
confidence: 96%
“…Topics also include the effect of fertilization on establishment (Lindsey, Thoms, & Christians, 2020;Øgaard & Aamlid, 2020) and maintenance strategies for disease control (Hempfling, Murphy, & Clarke, 2020;Mattox, Kowalewski, McDonald, Lambrinos, & Pscheidt, 2020). Findings on turfgrass performance under different irrigation strategies are reported by Serena et al (2020) and Dyer et al (2020). We would like to thank Dr. John Stier, University of Tennessee, and Dr. Mike Richardson, Agronomy Journal.…”
mentioning
confidence: 99%